Extending System Readiness Levels to Assess and Communicate Human Readiness. Issue 2 (March 2016) - Miller, Michael; Thomas, Seth; Rusnock, Christina
ABSTRACT: Program managers need to understand the maturity of all aspects of their system to make intelligent investment decisions during product development. Technology Readiness Levels (TRL) are regularly applied to classify and communicate the state of technology development and to guide investment during technology and system development. This concept has recently been extended to include integration readiness to understand the maturity of the interfaces between technology components in a system. However, these methods do not consider whether human interfaces to the system have been fully matured. The current research extends the TRL and Integration Readiness Level (IRL) concepts to include the human elements of the system. The method proposes two concepts: the Human Capability Level and the Human IRL. The Human Capability Level refers to the capability of a system to reliably provide well equipped personnel with sufficient skills and the ability to perform successfully with the system. The Human Integration Readiness Level refers to the demonstration of effective human integration with system technologies. Each of these concepts are then combined with previous work to demonstrate the development of a System Readiness Level, which includes technology and human elements. We show that these Human Capability and Integration Level concepts can be used in conjunction with the existing TRL and IRL concepts to compare the relative maturity of components of the system for supporting each class of human users as well as performing its technical functions.